2020
DOI: 10.1111/liv.14645
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and long‐term outcome of sub‐clinical primary sclerosing cholangitis in patients with ulcerative colitis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…16 This may be attributable to increased awareness and better diagnostics driving recognition of subclinical sclerosing cholangitis in patients with IBD. 31,32 Indeed, data from Norway show that in a cohort of 322 patients with IBD, 17 individuals developed overt biliary lesions on cholangiography despite normal liver biochemistry. 31 Moreover, crosssectional data from the UK found that up to 14% of patients with IBD manifest radiologic features of sclerosing cholangitis in the face of normal alkaline phosphatase values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This may be attributable to increased awareness and better diagnostics driving recognition of subclinical sclerosing cholangitis in patients with IBD. 31,32 Indeed, data from Norway show that in a cohort of 322 patients with IBD, 17 individuals developed overt biliary lesions on cholangiography despite normal liver biochemistry. 31 Moreover, crosssectional data from the UK found that up to 14% of patients with IBD manifest radiologic features of sclerosing cholangitis in the face of normal alkaline phosphatase values.…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, crosssectional data from the UK found that up to 14% of patients with IBD manifest radiologic features of sclerosing cholangitis in the face of normal alkaline phosphatase values. 32 This growing body of data indicates that even the most contemporary of population-based estimates may underestimate the incidence of PSC by a considerable margin.…”
Section: Discussionmentioning
confidence: 99%
“…However, many people with PSC likely remain undiagnosed. [40,41,[152][153][154] Patient demographics and PSC phenotype influence disease progression. Younger age at diagnosis and female sex are associated with better outcomes.…”
Section: Natural History Of Pscmentioning
confidence: 99%
“…A large population study revealed that patients with long‐standing IBD had a threefold higher prevalence of PSC on magnetic resonance cholangiopancreatography (MRCP) imaging than would have been detected via symptomatic assessment 22 . Furthermore, two studies have shown that biochemical (alkaline phosphatase) levels may not increase over time in those with subclinical PSC 22,23 . As such, these patients may never undergo cross‐sectional screening as a lack of biochemical elevation would classically signal to physicians that PSC has been ruled out.…”
Section: Discussionmentioning
confidence: 99%